Causal association between rheumatoid arthritis and celiac disease: A bidirectional two-sample mendelian randomization study - Hua, Lijiangshan; Xiang, Shate; Xu, Rixiang; Xu, Xiao; Liu, Ting; Shi, Yanan; Wu, Lingyun; Wang, Rongyun; Sun, Qiuhua (Frontiers in Genetics, 2022)
Objectives: Rheumatoid Arthritis (RA) has been associated with Celiac Disease (CD) in previous observational epidemiological studies. However, evidence for this association is limited and inconsistent, and it remains uncertain whether the association is causal or due to confounding or reverse causality. This study aimed to assess the bidirectional causal relationship between RA and CD. Methods: In this two-sample Mendelian randomization (MR) study, instrumental variables (IVs) for RA were derived from a genome-wide association studies (GWAS) meta-analysis including 58,284 subjects. Summary statistics for CD originated from a GWAS meta-analysis with 15,283 subjects. The inverse-variance weighted (IVW) method was used as the primary analysis. Four complementary methods were applied, including the weighted-median, weighted mode, MR pleiotropy residual sum and outlier (MR-PRESSO) test and MR-Egger regression, to strengthen the effect estimates. Results: Positive causal effects of genetically increased RA risk on CD were derived [IVW odds ratio (OR): 1.46, 95% confidence interval (CI): 1.19-1.79, P = 3.21E-04]. The results of reverse MR analysis demonstrated no significant causal effect of CD on RA (IVW OR: 1.05, 95% CI: 0.91-1.21, P = 0.499). According to the sensitivity analysis, horizontal pleiotropy was unlikely to distort the causal estimates. Conclusion: This study reveals a causality of RA on CD but not CD on RA among patients of European descent. This outcome suggests that the features and indicators of CD should regularly be assessed for RA patients.